Lateral damage and point of impact in intersection crashes: Implications for injury - Chipman, Mary L.; Lebovic, Gerald; Desapriya, Ediriweera; Gane, John (Assurances et gestion des risques / Insurance and Risk Management, 2006)
Crashes in intersections may result in damage to vehicles and injury to occupants in many different ways. One vehicle hitting the side of another (T-type) is the classic side impact; however, we have argued in the past that other crash configurations (e.g., L-type) may subject occupants to similar risks because both vehicles may sustain lateral damage. To test this assumption, we examined crash data from police reports of 4032 intersection right-angle crashes (IRC), collected by the Insurance Corporation of British Columbia for 2002. We compared the risk and types of injury in target and bullet vehicles for T-type crashes, L-type crashes by front and rear fender involvement and for all other IRC crashes. There were 787 T-type crashes (impact into either side of target vehicle), compared to 798 L-type crashes (impact into front fender) and 350 L-type (impact into rear fender). Overall, injury risk was 23.5%. Proportions injured were very similar for occupants of target and bullet vehicles in T-type crashes (OR = 0.996; 95% ci 0.80 to 1.24.); for L-type crashes, the proportions were 23.2% for front and/or front fender involvement and 15.0% for crashes involving the rear fender of one vehicle and the front or front fender of the other (OR =1.71; 95% ci 1.40 - 2.10). Apart from rear fender crashes, proportions injured were very similar (P > 0.05). Other factors, notably weather, lighting, land use and vehicle damage differed significantly by crash type, and were strongly associated with injury risk. Since rear-fender crashes are a small proportion of IRC crashes, this suggests that it is not necessary to subdivide crashes by configuration in IRC crashes.